2017
DOI: 10.18203/2394-6040.ijcmph20175359
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and factors associated with it in geriatric population in rural area of Vadodara, Gujarat

Abstract: Background: Geriatric depression is becoming a global public health problem causing considerable morbidity and disability. This problem is also increasing in India but still not sufficient work has been done on depression in many parts of India. This study aimed to find out prevalence of and factors associated with depression in elderly population in Vadodara, Gujarat.Methods: A community based cross sectional study was performed among 176 participants of more than 60 years of age. Simple random sampling was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In the current study, the overall prevalence of depression among the elderly was found to be 76% which was similar to the findings of a study done by Suganathan and Thilak et al 5,6 In this study elderly females with depression were more compared to males, similar to the results in a study in Vadodara and Chittoor. 7,3 In rural areas, females are not getting much importance than mails and studies prove that they are much more neglected in their old age which can lead to increased depression in elderly females. Our study also shows that depression was more common among 65-69 years of age, this result was similar to the study conducted in a rural population of Tamilnadu.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the overall prevalence of depression among the elderly was found to be 76% which was similar to the findings of a study done by Suganathan and Thilak et al 5,6 In this study elderly females with depression were more compared to males, similar to the results in a study in Vadodara and Chittoor. 7,3 In rural areas, females are not getting much importance than mails and studies prove that they are much more neglected in their old age which can lead to increased depression in elderly females. Our study also shows that depression was more common among 65-69 years of age, this result was similar to the study conducted in a rural population of Tamilnadu.…”
Section: Discussionmentioning
confidence: 99%
“…Chalise and Rai [7] found that 29.7% Nepalese rai older adults in the Kathmandu valley were depressed. Jadav and Patel [11] found 34.1 % depression among senior population in rural area of Vadodara, Gujrat and Pilania, Yadav [12] found 34.4% depression among Indian elderly population. However, some studies contradict our findings: a study conducted among elderly people in a rural south Indian community found 12.7% [13], a study conducted in north India 9.5 % [14], a study conducted in Thailand 18.5% [15] ,and a study conducted in Nepal among older adults found 15.4% [16] which is lower than my study and some were higher than our study; a study conducted by Vol.12; Issue: 1; January 2022 Shrestha, Shrestha [6] in the emergency department of teaching hospital in Nepal found 45.7 % prevalence of geriatric depression, Jemal, Hailu [17] found 54.5 percent, and a study conducted by Simkhada, Wasti [18] among older adults in Kathmandu Nepal found 60.6%.…”
Section: Discussionmentioning
confidence: 95%
“…Score 1 showed that the answer to the question awarded one point for depressed symptoms, while a score of 0 indicated that no point was awarded. Depression symptoms were classified as normal (0-4), mild (5-8), moderate (9)(10)(11) and severe (12)(13)(14)(15). [2] This tool had already used in Nepal.…”
Section: Data Collection: Tools and Techniquesmentioning
confidence: 99%